Fitting parsimonious household- portfolio models to data - Sylwia Hubar; Christos Koulovatianos; Jian Li (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
US data and new stockholding data from fifteen European countries and China exhibit a common pattern: stockholding shares increase in household income and wealth. Yet, there is a multitude of numbers to match through models. Using a single utility function across households (parsimony), we suggest a strategy for fitting stockholding numbers, while replicating that saving rates increase in wealth, too. The key is introducing subsistence consumption to an Epstein-Zin-Weil utility function, creating endogenous risk-aversion differences across rich and poor. A closed-form solution for the model with insurable labor-income risk serves as calibration guide for numerical simulations with uninsurable labor-income risk.
urn:nbn:de:hebis:30:3-343710
Keywords: G11; D91; D81; D14; D11; E21; 330; Epstein-Zin-Weil recursive preferences; subsistence consumption; household-portfolio shares; business equity; wealth inequality